Pengaruh Flushing Berbasis Pakan Lokal terhadap Pertumbuhan dan Birahi Kambing Kejobong Betina Dewasa - Socheh, M; Ismaya, Ismaya; S. Budisatria, I G; Kustantinah, Kustantinah (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2011)
The purposes of this study were to: 1. Study whether flushing based local feed affect growth of Kejobong doe. 2. Study whether flushing based local feed affect the response of estrous, the initial of estrous, and the length of estrous. Twenty Kejobong does with average initial live weight 26.6 ± 1.7 kg were used in this study. The animals were placed randomly into two feed treatments, namely: non-flushing (p0) and flushing feed (p1) with 10 replicates each. The observed variables were ADG, estrous response, the initial of estrous and the length of estrous. The difference value observed for the treatment of non-flushing and flushing analyzed by t test. The results showed that the growth of Kejobong doe at flushing group was higher (P≤0.05) than non-flushing group. Response of estrous both in the group of nonflushing and flushing were 100%. The initial of estrous of Kejobong doe from flushing group was more quickly than non-flushing (P≤0.05). The length of estrous of flushing group waslonger (P≤0.05) than non-flushing group. It can br concluded that flushing on Kejobong doe can improve growth, accelerate the initial of estrous and prolong the length of estrous.Key words: flushing, non-flushing, growth, estrous, Kejobong doe